Advocate Anomalies in Money Laundring Practices in Indonesia: Analysis of Legal System Theory to Reporting Function in Government Regulation No. 43 Year 2015 - Lubis, Fauziah (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on how anomalies advocate in money laundring practices in Indonesia by providing analysis of the law and reporting functions in government regulation No. 43 year 2015. Government Regulation No. 43 year 2015 is obliging the advocate profession to report suspicious financial transactions to the PPATK. This research also aims to determine the implementation of PPATK in carrying out its duties as one of the institutions that supervise the travel flow of financial funds in Indonesia, especially from various professions that have potential harm to the country, Besides, also know the policies and applications and attitudes of the advocacy profession who are often involved in the practice of money laundring, as well as the conflict of interest that occurs from the PPATK with the advocate. This certainly caused PPATK to see the flow of funds often clash between the law and government regulation number 43-year 2015. With this law the confidentiality of the advocate profession has been assured, because the advocate has an internationally known lawyer-client privilege principle, which is not to convey the Considered confidential (confidential) except for the permits or orders of his clients so feared from this clash suspected the occurrence of business to do money laundring practices.